Bushenjianpi formula combined with entecavir for HBeAg-negative chronic hepatitis B patients: a multicentre, randomised, double-blind, placebo-controlled trial. (October 2016) - Gao, Yue-Qiu; Zhang, Xin; Li, Man; Zhou, Zhen-Hua; Sun, Xue-Hua; Zhu, Xiao-Jun; Jin, Shu-Gen
Abstract: Background: The treatment combination of traditional Chinese medicine with western medicine results in significant decrease of serum hepatitis B virus (HBV) DNA and increase of HBeAg loss in patients with HBeAg-positive chronic hepatitis B (CHB) without any serious adverse events. We aimed to assess whether the Bushenjianpi Formula combined with entecavir could increase the HBsAg loss rate in patients with HBeAg-negative CHB. Methods: In this multicentre, randomised, double-blind, placebo-controlled trial, we recruited patients with HBeAg-negative CHB from ten third-level grade-A hospital of Traditional Chinese Medicine. The inclusion criteria included a history of HBV or HBsAg positive for more than 6 months; positivity for HBsAg or HBV DNA; persistent HBeAg-negativity or HBeAb positivity; HBV DNA concentration of 1 × 10 4 copies per mL or higher by PCR assay at least 4 weeks before screening; alanine aminotransferase (ALT) concentrations of 2 × ULN or greater, or 1 × ULN≤ALT<2 × ULN and Knodell histology activity index of 4 points or greater at least 4 weeks before screening; no treatment with any nucleoside analogues or interferon at least 12 months before screening; and age 18–65 years. The exclusion criteria included being co-infected with other hepatitis viruses; hepatocellular carcinoma and other forms of liver disease; having other severe primary disease or mental disorder disease, and being pregnant and lactating. By using a block randomisation method, patients were randomly assigned (1:1) to receive Bushenjianpi Formula combined with entecavir (treatment group) or placebo combined with entecavir (control group) for 96 weeks. All patients were treated with entecavir 0·5 mg daily and the Bushenjianpi Formula or placebo (4·5 g twice daily, oral administration). The primary outcome was the of rate of HBsAg negative conversion and the secondary outcomes were the decline range of HBsAg, and the level of cccDNA. We used χ 2 tests and independent-sample t -test to assess differences between groups. This study was conducted in accordance with the ethics principles of the Declaration of Helsinki and approved by the Ethical Committee of Shuguang Hospital, Shanghai University of Traditional Chinese Medicine. All patients were written informed consent. Findings: Between Dec 1, 2012, and March 31, 2016, 620 patients with HBeAg-negative CHB were recruited, and they were randomly assigned to the treatment group (320 patients) and the control group (320 patients). After 96 weeks of treatment, the percentage of patients who had reduction in serum HBsAg concentrations decreased more than 1Log10 in the treatment group (11·76%), which was significantly higher than that in control group (6·41%; p=0·043). The rate of HBsAg negative conversion was determined by the ratio between the number of patients whose HBsAg level was lower than 0·1 IU/mL and the total number of patients in every group after treatment. The rate of HBsAg negative conversion was significantly greater in the treatment group (5·13%) than in control group (2·10%; p=0·046). The cccDNA level of liver tissue after treatment was lower than that before treatment in both groups (p=0·001). In this study, there were five cases of adverse events in treatment group and six cases of adverse events in control group. The symptoms in adverse events included cold, fever, and diarrhoea. Interpretation: The combination of Bushenjianpi Formula with entecavir could result in a decrease of serum HBsAg and liver tissue cccDNA, as well as increase of HBsAg negative conversion for patients with HBeAg-negative CHB. Funding: National Natural Science Foundation of China (81473477, 81403354, 81473629, 81403351, 81503545), Science Research Project of Twelve Five-year Plan (2012ZX10005004–002), Shanghai Rising-Star Program (13QA1403500), the Key Technology Research of Shanghai Municipal Science (13401902900), Three-year action plan of development of TCM in Shanghai (ZYSNXD-CC-ZDYJ015 and ZY3-CCCX-3–3027), Training plan of outstanding young medical talents, Shanghai Municipal Health Bureau (XYQ2013093), Shanghai Sailing Program (14YF1411600, 15YF1412300), Wang Baoen liver fibrosis research fund of China foundation for Hepatitis Prevention and Control (CFHPC20131045, CFHPC20131046) and the Budgeted Projects of Shanghai University of Traditional Chinese Medicine (2013JW40, 2014YSN39).